Banking Merger Policy In Indonesia: An Islamic Perspective - Ainul Fatha Isman (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2025)
This study aims to analize the banking merger policy based on Islamic perspective in Indonesia. This research uses a descriptive qualitative method. This research is a literature study approach. Data collection was obtained, retrieved, analyzed and cited from various sources through books or research results, documents and journals that are relevant to this research. This study shows that Banking mergers in Indonesia have been regulated in several regulations as the basis for allowing this policy, especially in Sharia banking. From an Islamic perspective, Sharia banking mergers should refer to Islamic economic philosophy. Islamic banking recognizes the importance of efficiency and competition. Still, the pursuit of interests in maximizing profits should be managed to promote socio-economic justice, prosperity, and benefit. Sharia banking in post-merger Indonesia, in carrying out its functions, needs to refer to the principles that are expressly stated in statutory regulations, such as social functions, and remains based on Sharia principles. This research has implications to the policy concerning Sharia banking mergers, which should consider maslahah and religious law aspects.